Methods of Purposeful English Teaching: Analysis and Results (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the methods of purposeful English teaching and evaluates their effectiveness. English has become a widely used and global language of communication around the world today. Therefore, it is very important to choose effective methods in teaching English. The article discusses the main methods used in teaching English, such as the communicative approach, the direct method, the audiolinguistic method, and private curricula. By comparing these methods with teaching practice and changes in the education system, the article attempts to evaluate effective strategies for teaching English and their results. As a result of the article, recommendations are made to identify the most effective methods of teaching English and to widely introduce them in the education system.